A Bioresistant Nitroxide Spin Label for In‐Cell EPR Spectroscopy: In Vitro and In Oocytes Protein Structural Dynamics Studies. Issue 5 (8th January 2018) - Karthikeyan, Ganesan; Bonucci, Alessio; Casano, Gilles; Gerbaud, Guillaume; Abel, Sébastien; Thomé, Virginie; Kodjabachian, Laurent; Magalon, Axel; Guigliarelli, Bruno; Belle, Valérie; Ouari, Olivier; Mileo, Elisabetta
Abstract: Approaching protein structural dynamics and protein–protein interactions in the cellular environment is a fundamental challenge. Owing to its absolute sensitivity and to its selectivity to paramagnetic species, site‐directed spin labeling (SDSL) combined with electron paramagnetic resonance (EPR) has the potential to evolve into an efficient method to follow conformational changes in proteins directly inside cells. Until now, the use of nitroxide‐based spin labels for in‐cell studies has represented a major hurdle because of their short persistence in the cellular context. The design and synthesis of the first maleimido‐proxyl‐based spin label (M‐TETPO) resistant towards reduction and being efficient to probe protein dynamics by continuous wave and pulsed EPR is presented. In particular, the extended lifetime of M‐TETPO enabled the study of structural features of a chaperone in the absence and presence of its binding partner at endogenous concentration directly inside cells. Abstract : The right label : A maleimido‐proxyl based nitroxide label resistant to reduction in a cellular environment was investigated. It allows structural dynamics of a chaperon protein to be followed in the absence/presence of its binding partner in vitro and inside cells and at endogenous concentration (ca. 20 μm ) by EPR spectroscopy.